2021
DOI: 10.1002/er.7463
|View full text |Cite
|
Sign up to set email alerts
|

Graphite felt modified withWO3,SnO2,and binaryWO3/SnO2‐mixtures as novel positive electrodes for cerium‐based redox flow batteries

Abstract: Cerium-based redox flow batteries (RFBs) such as Zn-Ce and V-Ce have received attention as attractive energy storage systems due to their high opencircuit cell voltages. To date, the most successful Ce-based RFBs have relied on expensive Pt-based positive electrodes. In this study, the use of more economical polyacrylonitrile (PAN)-based graphite felt (GF) containing tungsten oxide (WO 3 ) and/or tin oxide (SnO 2 ) nanocatalysts is examined for its electrochemical activity for the Ce(III)/Ce(IV) redox reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…By comparing the spectra, it was found that all samples exhibited inherent Ni, Co, and Mn characteristic peaks, while the samples added with WO 3 exhibited obvious W element characteristic peaks, indicating that the single-crystal ternary material successfully achieved WO 3 addition. Cyclic and rate performance tests were conducted on each sample in an electrochemical window of 2.8-4.4 V at room temperature [33]. All cycle and rate performance analyses are shown in Figure 8.…”
Section: Analysis Of Crp and Xpsmentioning
confidence: 99%
“…By comparing the spectra, it was found that all samples exhibited inherent Ni, Co, and Mn characteristic peaks, while the samples added with WO 3 exhibited obvious W element characteristic peaks, indicating that the single-crystal ternary material successfully achieved WO 3 addition. Cyclic and rate performance tests were conducted on each sample in an electrochemical window of 2.8-4.4 V at room temperature [33]. All cycle and rate performance analyses are shown in Figure 8.…”
Section: Analysis Of Crp and Xpsmentioning
confidence: 99%
“…The high cost and limited durability of platinum, as well as problems with remixing and rebalancing the electrolytes during cycling, were probably the main reasons for Plurion's eventual liquidation. Although there has been some interest in revising Zn-Ce RFBs recently, 160,161 this technology is considered as a "no-go" by most RFB developers.…”
Section: Introduction and Zinc-halogen Batteriesmentioning
confidence: 99%